حماية الطفل في القانون الإندونيسي والفقه الإسلامي (دراسة مقارنة)(Perlindungan Anak Studi Komparatif Undang-Undang dan Fiqh Islam) - Sudarto, Sudarto, Dr.Muindinillah Basri, M.A (2013)
The thesis in title: The protection of child in the Indonesian law and Islamic jurisprudence (Comparative Study). Research problem of thesis There are a numbers of violence toward children or abaut their rights in Indonesian society. Study objectives to explain about the definition of child, principles, law sources, and implementation of child protection in the Indonesian law and the Islamic jurisprudence? Also to explain of children's rights, a kind of punishment for trespasser of children's rights, Finally, to explain about similarities and differences between Indonesia law and Islamic jurisprudence in the child protection affair. Research methodology used of thesis Analytical deductive comparative model. Main results of thesis are the child according to Indonesian law is every child has not been 18 years old and also the child who is still in the womb. while according to Islamic jurisprudence the child is every child has not been baligh, baligh can be known by natural and age signs. Principles and law sources of child protection in Indonesian law is only the result of human mind and not based on revelation, while principles and law sources of child protection in Islamic jurisprudence based on revelation in the holly Quran and Sunnah or ijtihad which is based on revelation in the Ijma and Ijtihad. The implementation of child protection in Indonesion law pays more attention to physical and intellec needs, while in Islamic jurisprudence pays more attention to physical and spiritual that invalues primary, secondary and tertiary needs. The rights of the child who has not been born those acknowledged by Indonesian law i. e life and obtaining the health insurance rights, while in Islamic jurisprudence i.e life and obtaining the health insurance, descendant and ownership rights. Indonesian law and Islamic jurisprudence acknowledge the majorities of the children rights after being born but Islamic jurisprudence has more value then Indonesion law from the side of attention to the new birth by giving primary care and acknowledging the suckle, orphan, and finding child rights. Indonesian law oblige Indonesion children some compulsories but Islamic jurisprudence do not, because they are not baligh yet. Islamic figh has more specials things then Indonesion law from the side of varions of punishment by keeping paying attention not only to the benefit of offenders, victims and community but also to the size of the crime